2005
DOI: 10.1128/jb.187.13.4573-4583.2005
|View full text |Cite
|
Sign up to set email alerts
|

Epimerase Active Domain of Pseudomonas aeruginosa AlgG, a Protein That Contains a Right-Handed β-Helix

Abstract: The polysaccharide alginate forms a protective capsule for Pseudomonas aeruginosa during chronic pulmonary infections. The structure of alginate, a linear polymer of ␤1-4-linked O-acetylated D-mannuronate (M) and L-guluronate (G), is important for its activity as a virulence factor. Alginate structure is mediated by AlgG, a periplasmic C-5 mannuronan epimerase. AlgG also plays a role in protecting alginate from degradation by the periplasmic alginate lyase AlgL. Here, we show that the C-terminal region of AlgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 83 publications
(120 reference statements)
0
25
0
Order By: Relevance
“…In vivo studies of P. aeruginosa AlgG revealed that mutagenesis of each of the residues in the conserved DPHD motif (residues 317-320 in P. syringae) abolished epimerase activity (53). This motif is part of the carbohydrate-binding/sugar hydrolysis domain and is proposed to be part of the active site (22,53,55).…”
Section: Algg Adopts a Right-handed Parallel ␤-Helixmentioning
confidence: 99%
“…In vivo studies of P. aeruginosa AlgG revealed that mutagenesis of each of the residues in the conserved DPHD motif (residues 317-320 in P. syringae) abolished epimerase activity (53). This motif is part of the carbohydrate-binding/sugar hydrolysis domain and is proposed to be part of the active site (22,53,55).…”
Section: Algg Adopts a Right-handed Parallel ␤-Helixmentioning
confidence: 99%
“…On average, the enzyme epimerizes 10 units ((MG) 10 ) in each reaction before leaving the chain (19). An alignment of all known mannuronan C-5-epimerase sequences from bacteria and algae showed that they share an YG(F/I)DPH(D/E) motif (residues 149 -155 in AlgE4) (21)(22)(23). Asp 152 of this motif, which is also conserved in some pectate lyases, has been shown to be important for activity in AlgE7 (21).…”
mentioning
confidence: 99%
“…P. aeruginosa mannuronan epimerase is not closely related to the A. vinelandii enzymes, and although its activity has been reported to be Ca 2+ -dependent, that aspect of the reaction has not been examined in detail. Sequence analysis and homology modeling of the P. aeruginosa epimerase suggests that the epimerase domain of the protein is a right-handed β-helix, which is characteristic of enzymes that utilize polysaccharides as substrates (14). A variety of kinetic studies are presented here, which provide insight into the interactions between the epimerase and alginate.…”
mentioning
confidence: 99%